Evaluating sources of scientific evidence and claims in the post-truth era may require reappraising plausibility judgments. Issue 3 (2nd July 2020) - Sinatra, Gale M.; Lombardi, Doug
Abstract: When individuals have questions about scientific issues, they often search the Internet. Evaluating sources of information and claims they find has become more difficult in the post-truth era. Students are often taught source evaluation techniques, but the proliferation of "fake news" has resulted in a misinformation arms race. As searchers get more sophisticated identifying misleading information, so do purveyors of information who intend to mislead. We draw on a theoretical model of plausibility judgments and current theory and research in source evaluation to suggest that the post-truth era elevates the need for critical evaluation of online information about scientific issues. We argue that explicitly reappraising plausibility judgments may be a crucial addition to evaluating the connections between sources of information and knowledge claims. Individuals who search for and read a scientific article online should ask themselves: Is this explanation plausible, and how do I know?